Улогата на човечкиот капитал во економскиот раст со посебен осврт на Република Северна Македонија - Цветаноска, Маријана (Економски факултет, УКИМ, Скопје, 2021)
The role of human capital in the growth process of any country is of a great importance. As a special factor of production contributes for solving key economic problems, especially in an economy that in the process of globalization is based on knowledge. The aim of this dissertation is to present the role and examine the impact of human capital on economic growth in North Macedonia in the period from 2000 to 2019 by using econometric analysis of time series of human capital indicators that are widely accepted in theory and empirical research. It is about education and health, measured through the expenditures on education and health. In the doctoral dissertation, the Lucas model is applied. For the purpose of this dissertation, regression analysis (OLS method) is performed followed by examination of the stationarity of the series, as well as examination of the necessary conditions for selection of the best model from the available alternatives. This dissertation also attempts to determine whether there is a causality, i.e a cause-and-effect relationship between human capital and economic growth, and if so in which direction. Hence, the Granger causality test is used to examine the cause-and-effect relationship. The results show that there is a positive relationship between human capital and economic growth in North Macedonia, and that there is a cause-and-effect relationship between them. The doctoral dissertation contributes to the wider literature on the importance of human capital for economic growth. It also emphasizes the importance of the accumulation of human capital in North Macedonia, showing that formal education and health are important factors in understanding the role of human capital in the process of economic growth. The recommendations from the doctoral dissertation are in the direction of education, but also of health to be seen as a healthy economic investment, which raises not only the quality of life, but also improves the labor market and hence the growth in the country. Such implications are important and should be taken into account when making future decisions by macroeconomic policy makers.
Докторска дисертација одбранета во 2021 година на Економскиот факултет во Скопје, под менторство на проф. д–р Предраг Трпески.
Keywords: economic growth, education, health, human capital, North Macedonia